Impact of Parental Involvement and Educational Status on Primary School Children's Academic Achievement - Okeke Tobechukwu Ebele (Britain International for Academic Research (BIAR) Publisher, 2024)
This work focused on the effects of parental involvement and education of the child on the academic performance of the primary school students in Otuocha education zone, Anambra state. The research adopted a descriptive survey research design to assess and provide the current profile of the sampled primary schools in the Otuocha education zone, Anambra State. A cross-sectional study was conducted among the students and teachers 13 253 respondents a sample of 200 participants was selected randomly from five schools. A structured questionnaire which has been developed based on the literature review, reviewed by experts, and reliability tested yielded index 0. 82 was employed to collect data. Measures of perceived influence of home environment on academic achievement were made using a 4-point Likert scale. The scores attained were analyzed with use of mean values with 2. It was hypothesized that there is positive influence when the Beta value is equal to or greater than 5. To make sure the questionnaires were completed fully, the researchers administered them and personally collected them. The study shows that the aspects of parental involvement that includes hiring home tutors, helping with homework exercises, and the provision of tutorial materials all are strong boosts to academic performance. On the other hand, parental neglect leads to poor performance in children's academic achievements. Furthermore, a study shows that higher parental education status has a positive effect on child academic performance as it enhances positive self images, self efficacy and cognitive skills of the learner. The above findings confirm that parental involvement and educational background are instrumental determinants of the academic achievement of primary school children.